Self-hypnosis for anxiety associated with severe asthma: a case report - Anbar Ran D (BMC, 2003)
Abstract Background Management of asthma can be complicated by both medical and psychiatric conditions, such as gastroesophageal reflux, chronic sinusitis, and anxiety. When symptoms of asthma are interpreted without regard to such conditions treatment may yield a suboptimal outcome. For example, anxiety-associated dyspnea, tachypnea, and chest tightness can be mistakenly interpreted as resulting from an exacerbation of asthma. Medical treatment directed only for asthma may thus lead to overuse of asthma medications and increased hospitalizations. Case Presentation The described case illustrates how a systemic steroid-dependent patient with asthma benefited from receiving care from a pediatric pulmonologist who also was well versed in the diagnosis and treatment of anxiety. By using self-hypnosis, the patient was able to reduce her dependence on bronchodilators. Following modification of her medical therapy under supervision of the pulmonologist, and regular use of hypnosis, the patient ultimately was weaned off her systemic steroid therapy. Conclusions This report emphasizes that anxiety must be considered as a comorbid condition in the treatment of asthma. Self-hypnosis can be a useful skill in the treatment of a patient with anxiety and asthma.